2006
DOI: 10.1097/01.qco.0000224820.19858.7a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to neonatal infection

Abstract: Despite the enormous human and financial costs of infection for neonatal mortality and morbidity worldwide, it remains unclear why neonates are so susceptible. Genetic epidemiologic studies may assist in the identification of critical protective and pathogenic pathways. Despite the current relative lack of robust data, such studies are likely to facilitate the development of interventions that ultimately decrease the significant morbidity and mortality of this highly vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
(66 reference statements)
0
7
0
5
Order By: Relevance
“…Complement factors and acute phase proteins, are important immune system mediators. They are critically important to prevent infections [1].…”
Section: Introductionmentioning
confidence: 99%
“…Complement factors and acute phase proteins, are important immune system mediators. They are critically important to prevent infections [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the fetus is vulnerable to infection because both cellular and humoral immunity are inadequately developed in intrauterine life [9]. Immature naïve T lymphocytes are normally the dominant phenotype in newborns [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Family studies, especially twin studies, and population studies have clearly shown a genetic component to susceptibility to infectious disease ( Frodsham and Hill, 2004 ;Lipoldova and Demant, 2006 ;Strunk and Burgner, 2006 ). Family studies, especially twin studies, and population studies have clearly shown a genetic component to susceptibility to infectious disease ( Frodsham and Hill, 2004 ;Lipoldova and Demant, 2006 ;Strunk and Burgner, 2006 ).…”
Section: Genetic Susceptibility To Pathogensmentioning
confidence: 99%